Sex Chromosome Turnover in Moths of the Diverse Superfamily Gelechioidea - Paladino, Leonela Z. Carabajal; Provazníková, Irena; Berger, Madeleine; Bass, Chris; Aratchige, Nayanie S.; Lopez, Silvia N.; Marec, Frantisek; Nguyen, Petr (Oxford University Press, 2019)
Sex chromosomes play a central role in genetics of speciation and their turnover was suggested to promote divergence. In vertebrates, sex chromosome-autosome fusions resulting in neo-sex chromosomes occur frequently in male heterogametic taxa (XX/XY), but are rare in groups with female heterogamety (WZ/ZZ). We examined sex chromosomes of seven pests of the diverse lepidopteran superfamily Gelechioidea and confirmed the presence of neo-sex chromosomes in their karyotypes. Two synteny blocks, which correspond to autosomes 7 (LG7) and 27 (LG27) in the ancestral lepidopteran karyotype exemplified by the linkage map of Biston betularia (Geometridae), were identified as sex-linked in the tomato leafminer, Tuta absoluta (Gelechiidae). Testing for sex-linkage performed in other species revealed that while LG7 fused to sex chromosomes in a common ancestor of all Gelechioidea, the second fusion between the resulting neo-sex chromosome and the other autosome is confined to the tribe Gnoreschemini (Gelechiinae). Our data accentuate an emerging pattern of high incidence of neo-sex chromosomes in Lepidoptera, the largest clade with WZ/ZZ sex chromosome system, which suggest that the paucity of neo-sex chromosomes is not an intrinsic feature of female heterogamety. Furthermore, LG7 contains one of the major clusters of UDP-glucosyltransferases, which are involved in the detoxification of plant secondary metabolites. Sex chromosome evolution in Gelechioidea thus supports an earlier hypothesis postulating that lepidopteran sex chromosome-autosome fusions can be driven by selection for association of Z-linked preference or host-independent isolation genes with larval performance and thus can contribute to ecological specialization and speciation of moths.
Keywords: Coleophora; Depressaria; Hofmannophila; Opisina; Phthorimaea; Sitotroga